Residential density, behavior and dengue haemorraghic fever (dhf) incidence in Surabaya, Indonesia - Ika Prastiani; Corie Indria Prasasti (Social Medicine Publication Group, 2020)
Dengue Haemorraghic Fever (DHF) has been one of the leading cause of morbidity and mortality in Indonesia. Surabaya has been one of the districts in East Java Province categorized as dengue endemic, particularly the Gunung Anyar Subdistrict. The purpose of this study is to analyze the relationship between the presence of larvae, residential density and public behavior, with the incidence of dengue in Gunung Anyar Village, Subdistrict of Gunung Anyar, Surabaya. The type of study is observational with cross sectional study design, with the primary data obtained from observation and interviews with 50 respondents, and the secondary data from The Local Health Clinics and Health Department. The samples are obtained with cluster random sampling. The results showed that variables related with the presence of larvae is residential density (p=0.018), knowledge (p=0.007) and attitude (p=0.000). However, the study found no correlation between the presence of larvae with the incidence of dengue (p=0.190). The study concludes that residential density and public behavior correlate with the larvae presence, but the larvae presence does not correlate with the incidence of dengue in Gunung Anyar Village, Surabaya. The Public Health Center and the Health Department should make innovation in method and public counseling media to increase public knowledge about dengue incidence and prevention.